Corporate social responsibility practices in Islamic banks - Mohd Sofian, Fatimah Noor Rashidah; Muhamad, Rusnah (Routledge, 2019)
Islamic banks are posited to have a strong position in the global financial market and have developed remarkably across various countries. However, the growth of Islamic banks worldwide is slowing down due to the volatility of the global financial market. To overcome such a problem, experts have suggested that Islamic banks become involved in corporate social responsibility (CSR) activities. Although there is extensive literature relating to CSR, the literature on CSR in relation to Islamic banks is still nascent. Therefore, the aim of this chapter is to explore CSR practices in Islamic banks. The review of the extant literature established that various stakeholders of Islamic banks perceived that CSR practices are important. However, the level of awareness concerning CSR practices is quite low. In addition, we feel that the CSR activities that are currently practised are inadequate and at odds with the objectives of Islamic economics. Therefore, in this chapter, we suggest that Islamic banks should adopt an integrated CSR framework based on the principles of Shariah (Islamic law) and ’urf (customs). This chapter contributes in providing an insight into the current CSR practices in Islamic banks.